Supervisi Kepala Sekolah Dalam Penggunaan Media Pembelajaran di Sekolah Dasar - Irianisyah, Srie; Harapan, Edi; Houtman, Houtman (CV. Creative Tugu Pena, 2020)
This study illustrated the implementation of supervision by school principals, particularly in the use of instructional media during the teaching and learning process in 90 Seberang Ulu II Palembang Primary Schools. This research method uses qualitative research methods and data collection is done by direct observation techniques in the field, documentation and interviews with teachers and school officials. The results showed that the implementation of academic supervision of the use of instructional media in Palembang 90 Primary School uses different techniques. To find out the use of instructional media objectively during the teaching and learning process, the Principal of State Elementary School 90 conducted a class visit supervision technique and also an individual meeting technique with a direct approach in accordance with a predetermined plan. There are factors that inhibit the implementation of academic supervision. The two factors influence the implementation of media use supervision learning in Palembang 90 Primary School. Nevertheless, all problems can be overcome until the supervision of the use of instructional media is carried out properly. Keywords: Supervision of the Pprincipals, Learning Media